Integrated transcriptomic and proteomic analysis of a cytoplasmic male sterility line and associated maintainer line in soybean - Wang, Dagang; Wang, Yanan; Zhang, Lei; Yang, Yong; Wu, Qian; Hu, Guoyu; Wang, Weihu; Li, Jiekun; Huang, Zhiping (Frontiers in Plant Science, 2023)
Heterosis is a critical phenomenon in crop improvement. Cytoplasmic male sterility (CMS) and Restorer gene (Rf) systems are essential components for heterosis-based breeding. However, the molecular mechanism underlying CMS remains largely unclear in soybean, an economically important crop, hindering the use of heterosis to enhance soybean productivity. To reveal the mechanism involved in CMS, we integrated a morphological investigation with comparative analyses of transcriptomic and proteomic changes in pollen from the CMS line W931A and its maintainer line, W931B, at the uninucleate microspore (UM) and binucleate pollen (BP) stages. Compared to W931B, which had healthy, oval pollen grains, W931A showed shrunken or degraded pollen grains with an irregularly thickened endothelium and decreased starch accumulation. Transcriptomic comparisons revealed a total of 865 differentially expressed genes (DEGs) in W931A over the two stages. These genes were primarily associated with pentose and glucuronate interconversions, sphingolipid metabolism, and glycerolipid metabolism. Proteomic analysis revealed 343 differentially expressed proteins (DEPs), which were mainly involved in carbon metabolism, glycolysis/gluconeogenesis, and nitrogen metabolism. Consistently, Gene Ontology (GO) biological process terms related to pollen development were enriched among DEGs at the UM and BP stages. Notably, four genes with demonstrated roles in pollen development were differentially expressed, including AGAMOUS-LIKE 104, PROTEIN-TYROSINE-PHOSPHATASE 1, and PHOSPHOLIPASE A2. A total of 53 genes and the corresponding proteins were differentially expressed in W931A at both the UM and BP stages, and many of these were pectinesterases, polygalacturonases, peroxidases, and ATPases. The results of this study suggest that pollen development in W931A is likely regulated through suppression of the identified DEGs and DEPs. These findings increase our understanding of the molecular mechanism underlying CMS in soybean, aiding future research into soybean fertility and promoting the efficient use of heterosis for soybean improvement.